2009
DOI: 10.3354/meps08283
|View full text |Cite
|
Sign up to set email alerts
|

Overlap between vulnerable top predators and fisheries in the Benguela upwelling system: implications for marine protected areas

Abstract: Industrial-scale fisheries are often thought to reduce food availability for top predators. It is essential to estimate the spatial and temporal overlap over a fine scale between fisheries and predators during their breeding season, when their energy demand is greatest and when they are most spatially constrained, in order to understand and manage this potential impact on their populations. In the Benguela upwelling region, 2 endemic vulnerable seabirds, Cape gannets Morus capensis and African penguins Sphenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 55 publications
1
57
0
Order By: Relevance
“…Finally, Cory's shearwater populations have a wide variety of potential wintering sites from which individuals may choose [28]. It is highly probable that the relative quality of each of these wintering quarters varies temporally as a consequence of physical forcing [30] and top-down processes, for example, fishing pressure [31]. This raises the question of whether Cory's shearwaters have enough plasticity in their migratory behaviour to quickly respond to such changes, which has important implications for their ability to adapt to longer term environmental shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Cory's shearwater populations have a wide variety of potential wintering sites from which individuals may choose [28]. It is highly probable that the relative quality of each of these wintering quarters varies temporally as a consequence of physical forcing [30] and top-down processes, for example, fishing pressure [31]. This raises the question of whether Cory's shearwaters have enough plasticity in their migratory behaviour to quickly respond to such changes, which has important implications for their ability to adapt to longer term environmental shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Their survival and breeding success are closely tied to the availability of pelagic sardines (Sardinops sagax) and anchovies (Engraulis encrasicolus) within 20-30 km of their breeding sites (Pichegru et al 2009). During their life, these fish can cover large distances (over hundreds of kilometres, Barange et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Developing reference control sites for comparison with fished sites is now vital for disentangling the confounding effects of climate change, fishing and changes in recovering marine mammal populations. Attempts to experimentally determine how fisheries deplete forage fish stocks and therefore impact dependent species have shown that fishing near-shore can increase the range of foraging trips and impact chick survival, leading to considerable change in population size (Bertrand et al, 2012;Pichegru et al, 2009;Sherley et al, 2015). Additionally, the foraging efficiency of breeding seabirds may be significantly affected by not only the regional quantity, but also the temporal and spatial patterns of prey removals.…”
Section: Wider Implications For Managementmentioning
confidence: 99%